The Effect of Competence, Commitment and the Work Environment on ManagementPerformance of CLC in The Bondowoso District CLC Forum - Holifah Holifah; Muhammad Firdaus; Yuniorita Indah Handayani (LPPM Institut Teknologi dan Sains Mandala, 2021)
The purpose of this study was to determine the effect of partially or simultaneously the variables of competence, commitment and work environment on the performance of PKBM managers Kab.Bondowoso, as well as to determine the ability of competency variables, organizational commitment and work environment in explaining performance variables. The number of samples in this study were 70 respondents. The analysis technique used is linear regression using SPSS 22.0. The results of data analysis showed that partially the competency, commitment and work environment variables had a significant effect on the performance of the PKBM managers in the District. Bondowoso. Simultaneously competence, commitment and work environment have a significant effect on the performance of PKBM managers Kab. Bondowoso. variable competency, work commitment and work environment have a contribution of 74.0% to the performance variable and the remaining 26.0% is influenced by other factors not included in the study. Keywords: Competence, Commitment, Work Environment, Manager Performance